1976
DOI: 10.1038/icb.1976.50
|View full text |Cite
|
Sign up to set email alerts
|

Ord River Arboviruses — Isolations From Mosquitoes

Abstract: Summary One hundred and thirty presumptive viruses have been isolated from 485 pools made from 23,872 mosquitoes collected in the Ord River area of North‐West Australia. One hundred and eleven of the virus isolates came from pools of Culex annulirostris, the dominant mosquito species caught in the vicinity of Kununurra. Forty‐five of the viruses pathogenic for newborn mice have been further characterized‐19 as Flaviviruses, 1 Alphavirus, 9 Koongol, 1 Mapputta and 15 non‐haemagglutinating viruses of which 6 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

1978
1978
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…The similarity of the Kimberley isolates with the Charleville and Toolamba isolates of 1974 suggests a spread from the north-west of Australia to the south-east. This contention is strengthened by the fact that the Kimberley is the only proven enzootic area in Australia (Liehne et al, 1976b;Wright et al, 1981).…”
Section: Resultsmentioning
confidence: 97%
“…The similarity of the Kimberley isolates with the Charleville and Toolamba isolates of 1974 suggests a spread from the north-west of Australia to the south-east. This contention is strengthened by the fact that the Kimberley is the only proven enzootic area in Australia (Liehne et al, 1976b;Wright et al, 1981).…”
Section: Resultsmentioning
confidence: 97%
“…The isolation data presented by Liehne et al (1976a) described a smaller number of isolates and, as such, could be presented in detail ( Table 2 of that publication). Further characterization of some of these early isolates revealed that several changes need to be made to the reported list of isolates.…”
Section: (B) Virus Isolationmentioning
confidence: 99%
“…The procedures used for the pooling of mosquitoes, isolation of viruses and identification of isolates have been described previously (Liehne et al, 1976a Liehne et al (1976c) and detailed collecting data from 1976 by Wright (1981). In total, 52,030 mosquitoes of 20 species have been processed into (Table 1).…”
Section: (B) Virus Isolationmentioning
confidence: 99%
See 2 more Smart Citations